MECHANICAL STATE ANALYSIS USING QUANTUM THEORY AND MATHEMATICAL MORPHOLOGICAL FILTER - SHI Ying (Jixie qiangdu)
Aiming at the erosion operator for the mathematical morphological filter（ MMF）,the quantum-inspired weighting structuring element（ QWSE） is proposed based on the quantum theory to extract fault information of mechanical vibration signal.Firstly,after analyzing the system with multiple quantum bits,a method which is employed to map the quantum space to the real number space is presented and the calculation formula of the QWSE is obtained. Then in order to compute all the parameters of the QWSE,the stochastic characteristics of mechanical vibration signal is utilized to acquire the quantum-inspired weighting while the local feature of signal is utilized to generate the dynamic height of the QWSE. Finally,the QWSE is appied to analyze the running status of bearing. The results indicate that QWSE can extract the fault period correctly.